DESAIN BAHAN AJAR PROGRAM LINEAR DENGAN PENDEKATAN KONTEKSTUAL BERBANTUAN LINEVER - Venissa Dian Mawarsari; Dwi Sulistyaningsih (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Teaching material is a tool for an educator in the success of the learning processat all levels of education and all areas of study. No exception learning process oflinear program in Higher Education. For that an educator must be able toarrange their own teaching materials in accordance with the competence to beachieved as well as student characteristics. In the course of linear programming,there needs to be a theory application in everyday problems or in industryproblems. In addition complex calculation problems make the process of solvingproblems related to linear program takes a long time. So that researchers doresearch in designing teaching materials linear program with linear assistedcontextual approach. So the purpose of this study is to know that the teachingmaterials linear program with linear-assisted contextual assisted approach usedin the learning process. Linever is an acronym for Lindo and Excel Solversoftware. The teaching materials developed are Diktat and Student Worksheet(LKM). This research is a part of development research with ADDIE developmentmodel (Analysis, Design, Development, implementation, Evaluation), that is atDesign stage. Data collection techniques use validation materials sheet given tothe validator. The result of the research shows that the linear program teachingmaterials with linearly validated contextual approach are used with the averagerating of 3.6% included in the criteria. Keywords: Teaching material, linear program, contextual , Lindo and Excel Solver